Psychological predictors of sports injuries in elite sky athletes: a multidimensional analysis of personality, anxiety, depression and inflexibility - Mogedano-Cruz, Sara; Clemente-Suárez, Vicente Javier; Jácome-López, Rafael; García-Sanz, Fernando; González-Fernández, Laura; González-de-la-Flor, Ángel; Romero-Morales, Carlos (Frontiers in Psychology, 2025)
IntroductionInjuries among elite alpine sky athletes can lead to both physical and psychological consequences. While previous studies have pointed out how emotional factors can influence the risk of injuries, there has not been much investigation into how different psychological elements relate to the overall injury burden.MethodsThis study aimed to evaluate how traits like neuroticism, anxiety, depression, psychological inflexibility, loneliness, and conscientiousness predict the frequency and severity of injuries in professional skiers. Additionally, it sought to identify psychological profiles that might indicate a higher risk of injury. We conducted a cross-sectional, observational, and analytical study involving 50 active professional alpine skiers. The data were analyzed using Poisson regression for injury frequency, multiple linear regression for perceived injury severity, and K-means cluster analysis to identify different psychological profiles.ResultsThe findings revealed that neuroticism [Exp (β) = 1.15, p = 0.026] and psychological inflexibility [Exp (β) = 1.09, p = 0.041] were significant predictors of injury frequency. Perceived injury severity was associated with depressive symptoms (β = 0.34, p = 0.009), inflexibility (β = 0.26, p = 0.034) and neuroticism (β = 0.21, p = 0.048). We identified three distinct psychological profiles: resilient, average and vulnerable, with the vulnerable group experiencing the highest injury burden (p < 0.05).ConclusionCertain psychological traits, especially neuroticism, inflexibility, and depressive symptoms are associated with an increased risk and severity of injuries. By identifying these psychological risk profiles, we can develop targeted interventions to prevent injuries and support recovery. It’s essential to incorporate psychological assessments into health and performance programs for athletes engaged in high-demand sports.